2014
DOI: 10.1055/s-0034-1390786
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness resection of gastric subepithelial tumors: a single-center series

Abstract: Endoscopic full-thickness resection of gastric subepithelial tumors with the suturing technique described above is feasible and effective. After the resection of gastrointestinal stromal tumors (GISTs), we did not observe any recurrences during follow-up, indicating that endoscopic full-thickness resection may be an alternative to surgical resection for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 15 publications
(15 reference statements)
0
38
1
1
Order By: Relevance
“…Since GISTs arise from the muscularis propria layer, established endoscopic resection techniques in the upper gastrointestinal tract (endoscopic mucosal resection, endoscopic submucosal dissection) can be expected to be associated with an increased risk of incomplete resection. Endoscopic full-thickness resection of the gastric wall has also been demonstrated to be feasible in single-center series [54,55], but as long as methods for postinterventional gastric wall closure are not standardized, these techniques must be considered as experimental. In contrast to gastric GISTs, transanal excision via transanal endoscopic microsurgery may be a safe alternative to transabdominal resection in small rectal GISTs [56,57,58].…”
Section: Management Of Localized Gistsmentioning
confidence: 99%
“…Since GISTs arise from the muscularis propria layer, established endoscopic resection techniques in the upper gastrointestinal tract (endoscopic mucosal resection, endoscopic submucosal dissection) can be expected to be associated with an increased risk of incomplete resection. Endoscopic full-thickness resection of the gastric wall has also been demonstrated to be feasible in single-center series [54,55], but as long as methods for postinterventional gastric wall closure are not standardized, these techniques must be considered as experimental. In contrast to gastric GISTs, transanal excision via transanal endoscopic microsurgery may be a safe alternative to transabdominal resection in small rectal GISTs [56,57,58].…”
Section: Management Of Localized Gistsmentioning
confidence: 99%
“…EFTR without laparoscopic assistance was performed as previously described [4,7]. The post-resection large defect was closed immediately by means of LeClamp TM endoloops and metallic clips and using a single-channel endoscope.…”
Section: Methodsmentioning
confidence: 99%
“…The latest National Comprehensive Cancer Network (NCCN) task force report has suggested that all GISTs 2 cm or larger should be resected [3]. With the progressive increase in experience in endoscopic submucosal dissection (ESD), endoscopic full-thickness resection (EFTR) without laparoscopic assistance has been applied to remove GISTs with extra-luminal growth and/or close proximity to the serosa [4][5][6][7][8][9]. The key step of the EFTR procedure is the complete closure of wall defects left by full-thickness resection and thereby avoiding surgical intervention.…”
mentioning
confidence: 99%
“…GERDX TM (G‐Surg, Seeon, Germany) is also a similar suturing device. Schmidt et al . demonstrated the feasibility of EFTR of gastric subepithelial tumors using NDO Plicator and GERDX.…”
Section: Endoscopic Full‐thickness Closurementioning
confidence: 99%